Conceptual and contextual perspectives on the modern law of treaties / edited by Michael J. Bowman, University of Nottingham, Dino Kritsiotis, University of Nottingham. - Bowman, Michael J.; Kritsiotis, Dino (Cambridge University Press, 2018)
In recent years there has been a flourishing body of work on the Law of Treaties, crucial for all fields within international law. However, scholarship on modern treaty law falls into two distinct strands which have not previously been effectively synthesized. One concerns the investigation of concepts which are fundamental to or inherent in the law of treaties generally - such as consent, object and purpose, breach of obligation and provisional application - while the other focuses upon the application of treaties and of treaty law in particular substantive (e.g. human rights, international humanitarian law, investment protection, environmental regulation) or institutional contexts (including the Security Council, the World Health Organization, the International Labour Organization and the World Trade Organization). This volume represents the culmination of a series of collaborative explorations by leading experts into the operation, development and effectiveness of the modern law of treaties, as viewed through these contrasting perspectives.